Analysis of the Experience of Using Augmented Reality Applications for Educational Tourism - Bahari, Astrid Octavia; Amol, Febriyanti; Pradana, Dominicus Wahyu; Iswanto, Dedy (LifeSciFi, 2025)
This study aims to systematically examine how Augmented Reality (AR) technology influences user experience in the context of educational tourism. The study was conducted using the Systematic Literature Review (SLR) method based on the PRISMA 2020 protocol, reviewing 13 selected scientific articles obtained from the Scopus database over the past ten years. The analysis was conducted using a thematic analysis approach, focusing on the dimensions of interactivity, perceived authenticity, user engagement, and learning effectiveness. The study findings indicate that the use of AR generally enhances the quality of educational experiences for tourists through immersive visual interfaces, integration of contextual narratives, and personalized content. Several theories, including TAM, SOR, UTAUT, and Perceived Authenticity, were consistently applied to explain the relationship between technology and user behavior. However, this study also identified significant challenges, including infrastructure limitations, low digital literacy, and the lack of integration of local cultural values in AR content development. Therefore, it is recommended to develop cross-sectoral strategies and more adaptive methodological approaches to the local context so that AR technology can be applied more widely and inclusively in supporting learning and cultural preservation in the educational tourism industry.